The successful development of a large-depth fixed-wing time-domain airborne electromagnetic survey system - Huang, Wei; Xiao, Du; Li, Junfeng; Ben, Fang; Li, Fei; Xu, Zhili; Cao, Zhanhong; Liu, Lei; Wu, Shan; Wang, Hao; Ding, Zhiqiang (Frontiers in Earth Science, 2025)
IntroductionThe fixed-wing time-domain airborne electromagnetic (FTDAEM) detection system is a geophysical exploration equipment carried on a fixed-wing aircraft, which detects underground electrical structures by transmitting and receiving transient electromagnetic fields. The FTDAEM systems hold a pivotal position in aerial geophysical exploration due to their exceptional endurance and high-efficiency survey capabilities. Although significant progress has been made in airborne electromagnetic technology, core technical details of various systems remain confidential.MethodsTo foster technological exchange and advancement in this field, our research team has, for the first time, fully disclosed the proprietary technology of the self-developed FTDAEM system (iFTEM-II). Building upon the 350-m detection depth achieved by the first-generation system (iFTEM-I), the team selected the Y12F aircraft platform with superior payload capacity and conducted comprehensive redesigns and research and development on all critical components, successfully developing a second-generation deep-detection system. This system has achieved multiple technological breakthroughs: (1) instantaneous kiloampere-level high-current, low-base-frequency large-moment transmission technology; (2) aircraft modification featuring externally mounted flexible transmitter coils and long-suspended receiver pods; (3) precise extraction technology for nanovolt-level weak signals in dynamic high-interference environments; and (4) high-volume data rapid processing and practical inversion technology.ResultsVerified by the actual exploration data, the effective detection depth of this system has reached 600 m. The successful development of the iFTEM-II system provides a reliable technical means for the rapid conduct of large-scale deep resource surveys.DiscussionThe open sharing measures of the system technology are conducive to promoting the progress of industry technology.